PENGARUH KOMPETENSI MENGGUNAKAN IT DAN KOMUNIKASI PEMASARAN TERHADAP KEUNGGULAN BERSAING E-COMMERCE BISNIS UMKM FASHION (Studi Kasus UMKM Jakarta Barat dan Tangerang Selatan) - Didin Hikmah Perkasa; Ahmad Juniarto Utomo; Zaenal Abidin (Jurnal Ilmiah Manajemen dan Bisnis, 2018)
This study about marketing and production of fashion. The purpose of this study is to knowinfluence competence use information technology and marketing communicationscompanies to competitive advantage e-commerce business UMKM fashion (case studyUMKM West Jakarta and South Tangerang). This research subject is person UMKM WestJakarta and South Tangerang. The sample used in this study is 125 respondents. Makingtechniques sample use convenience sampling. Therefore, the analysis of the data usedanalysis statistic in the form of SEM PLS. Research this study show that the competenceuse information technology significant effect competitive advantage and marketingcommunications significant effect competitive advantage.